Spatial Analysis of Tropical Cyclone Yaas using Satellite Data - Umakanth, N.; Gogineni, Rajesh; Mohan Rao, K. Madan; Reddy, B. Revanth; Ahammad, Sk. Hasane; Rao, M.C. (Malaysian Journal of Science, 2024)
Tropical cyclones are the major natural disasters in India. They cause high death toll and property destruction, that lead to a negative socioeconomic impact. For early warning alerts, real-time monitoring, impact and damage pre-assessment, and relief operations, remote sensing and geographic information systems (GIS) are helpful. Tropical cyclone warning bulletins detail the cyclone intensity, direction and position of occurrence of cyclonic event, velocity of the winds across the coastal areas, expected landfall site. During the period of May 23rd to May 28th, 2021, an attempt was made to examine Yaas cyclone over Bay of Bengal Sea (BOBS). Rainfall (RF), Convective available potential energy (CAPE), cloud top temperature (CTT), total precipitable water (TPW), lifted index (LI), convective inhibition (CIN), sea level pressure (SLP), divergence and sea surface temperature (SST) are used to analyze cyclonic activity. Cold dry air from high latitudes meet with warm moist air in low latitudes leading to instability. This instability is responsible for the conducive feature in convection occurrence. The weather research forecasting (WRF) model forecast results matched well with MERRA2 reanalysis results. The model performed well in prior occurrence of convection activity.